Characteristics of First-instar Nymphs in the Soft Scale Insects (Hemiptera: Coccidae): Surprising Indicators of Relationships (Bollettino di zoologia agraria e bachicoltura, 2024)
Recent studies of the adult males and immatures have shown that characteristics of these stages can provide some surprising indications of relationships within the soft scale insect family Coccidae. In this study of the taxonomic character~ in first-instar nymphs, characteristics of 120 species of first instars in eight of the ten subfamilies of Coccidae (Cardiococcinae, Ceroplastinae,Coccinae, Eriopeltinae, Eulecaniinae, Filippinae, Myzolecaniinae, and Pseudopulvinariinae) weere compared. Emphasis is placed on a comparison of some unusual features of first instars within the subfamily Myzolecaniinae and between the more typical characters seen in other first-instar soft scale insects.
Keywords: Coccidae; Scale Insects; Hemiptera; First lnstars